Evaluation of serum cathepsin B, D, and L concentrations in women with late-onset preeclampsia/Gec baslangicli preeklampside serum kathepsin B, D ve L duzeylerinin degerlendirilmesi - Ilhan, Gokce Anik; Yildizhan, Begum (Turkish journal of obstetrics and gynecology, 2019)
Objective: The aim of the study was to assess serum cathepsin B, D, and L concentrations in women with late-onset preeclampsia. Materials and Methods: One hundred forty pregnant women were enrolled in the study, of which 100 subjects were preeclamptic and 40 were healthy controls. Serum concentrations of cathepsin B, D, and L were measured and compared between the preeclamptic and control groups. Results: Cathepsin B and D concentrations were significantly higher in the preeclamptic group compared with the control group. There was no statistically significant difference between the groups in terms of cathepsin L concentrations. Cathepsin B concentrations were significantly higher in women with preeclampsia with severe features compared with those with preeclampsia alone. Conclusion: Women with late-onset preeclampsia have significantly higher serum cathepsin B and D concentrations than controls. Cathepsin B and D may be promising biomarkers in women with late-onset preeclampsia. Keywords: Cathepsin B, cathepsin D, cathepsin L, preeclampsia Amac : Bu calismanin amaci gec baslangicli preeklampside serum kathepsin B, D ve L duzeylerini degerlendirmektir. Gerec ve Yontemler: Calismaya 100 preeklamptik ve 40 saglikli olmak uzere 140 gebe hasta dahil edildi. Kathepsin B, D ve L serum duzeyleri olculerek, preeklamptik ve kontrol gruplari arasinda karsilastirildi. Bulgular: Serum kathepsin B ve D duzeyleri preeklamptik grupta kontrol grubu ile karsilastirildiginda anlamli olarak daha yuksek saptandi. Kathepsin L duzeyleri acisindan gruplar arasinda istatistiksel olarak anlamli bir fark yoktu. Kathepsin B duzeyleri siddetli preeklampsi bulgulari olan kadinlarda diger preeklamptik olgularla karsilastirildiginda istatistiksel olarak anlamli daha yuksek bulundu. Sonuc: Gec baslangicli preeklampsili kadinlarda serum kathepsin B ve D duzeyleri kontrol ile karsilastirildiginda anlamli olarak daha yuksekti. Gec baslangicli preeklampside kathepsin B ve D umut verici biyobelirtecler olabilir. Anahtar Kelimeler: Kathepsin B, kathepsin D, kathepsin L, preeklampsi